KEADILAN NORMATIF DANIMPLEMENTATIF TENTANG PENEGAKAN HUKUM EKONOMI SYARIAH UNTUK MEWUJUDKAN KEPASTIAN DAN KEADILAN HUKUM DI INDONESIA - Solehudin, Ending; Huda, Miftakhul; Ahyani, Hisam; Ahmad, Md Yazid; Abd Khafidz, Hasanah; Taufik Rahman, Encep; Hidayat, Moh. Syarif (Al-Risalah, 2024)
In Indonesia, sharia economic law is implemented through Religious Courts which have an important role in resolving disputes involving sharia financial entities such as banks, microfinance institutions, and insurance. Law Number 3 of 2006 replaces Law Number 7 of 1989 which significantly expands the authority of the Religious Courts in supervising and enforcing sharia economic principles. Sharia economics, which is based on Islamic values ​​such as justice, honesty, and legal certainty, forms an economic and financial system that is different from conventional systems. Religious Court Judges strive to balance ethical and practical considerations in carrying out their judicial duties. This research examines how ethical perspectives and practical considerations contribute to achieving legal certainty and justice in resolving sharia economic disputes, especially in the Surabaya Religious Court. This research uses a normative juridical approach using legal utility theory to analyze the challenges faced and propose strategies to increase the effectiveness of implementing simple, efficient, and cost-effective principles in Sharia economic protection at the Surabaya High Religious Court. The research results consider the principles of maqasid al-syariah to simplify the process, lighten the burden on the parties involved, and uphold justice in every decision-making. This study emphasizes the need for better integration between Islamic Sharia principles and Sharia banking practices in Indonesia, as well as encouraging reforms to ensure that legal outcomes provide fair justice and maximum social benefits, in line with the ethical and utilitarian aims of the law.